The Role of the Negative Regulation of Microglia-Mediated Neuroinflammation in Improving Emotional Behavior After Epileptic Seizures - Wu, Qiong; Wang, Hua; Liu, Xueyan; Zhao, Yajuan; Zhang, Junmei (Frontiers in Neurology, 2022)
Abstract Objective: Studies have long shown that uncontrolled inflammatory responses in the brain play a key role in the development of epilepsy.Microglia play an important role in epileptic-induced neuroinflammation, but their role after epileptic seizures is still poorly understood.Alleviating epilepsy and its comorbiditis has become a practical problem for pediatricians. Methods: A pilucapine-induced rat model of epilepsy was established. The rats were randomly divided into 4 groups: a control group, epilepsy group, TLR4 inhibitor group (epilepsy+TAK-242), and NF-κB antagonist group (epilepsy+BAY11–7082). Results: 1. The results of TUNEL staining showed that the expression of the Epilepsy group was the most obvious, significantly different from the Control , EP+BAY and EP+TAK group, respectively. 2. The expression of TLR4 and NF-κB was highest in the Epilepsy group and was significantly different from that in the Control , EP+BAY and EP+TAK group. 3. The expression of fluorescence intensity and positive cell number of IBA-1 in the Epilepsy group was highest and significantly different from the Control group, EP+BAY group and EP+TAK group, respectively. Western blot analysis of IBA-1 showed that the expression of Epilepsy group was highest and were statistically significant.4. CD68 were the highest in the Epilepsy group and were statistically significant. 5. In the open field experiment the central region residence time of the EP group was delayed , the central region movement distance was prolonged , the total distance was prolonged , the average speed was increased . Compared with the EP group , EP+BAY and EP+ TAK group was improved in different degrees.Conclusion: At the tissue level, downregulation of the TLR4/NF-κB inflammatory pathway in epilepsy can inhibit microglial activation and the expression of the inflammatory factor CD68, inhibit hyperphagocytosis, and inhibit the occurrence and exacerbation of epilepsy, thus improving postepilepsy cognitive and emotional disorders.